A novel homozygous c.1154+3_1151+6delAAGT mutation in CERKL causes autosomal recessive retinitis pigmentosa with a special phenotype in a consanguineous Tunisian Family - El Matri, L.; Falfoul, Y.; Habibi, I.; Turki, A.; Maamouri, R.; El Matri, K.; Chebil, A. (Acta ophthalmologica (Oxford, England), 2016)
Purpose The aim of our study was to assess the clinical phenotype and to determine the causative gene in a Tunisian family with an autosomic recessive retinitis pigmentose (arRP). Methods All accessible members of a consanguineous Tunisian family were included and underwent full ophthalmic examination with best corrected Snellen visual acuity, fundus photography, optical coherence tomography (SD‐OCT) and full field electroretinography (ERG). Index patient was selected for whole exome sequencing (WES) followed by homozygosity mapping. All detected variations were confirmed by direct Sanger sequencing. Results The clinical data of the patients showed typical hallmarks of RP symptoms for which affected individuals initially experienced night blindness with progressive visual loss and hemeralopia since the first decade of life. Visual acuity at baseline ranged from 1/10 to 5/10. Funduscopy revealed essentially mild optic disc and retinal atrophy and virtually no clumped pigmentation. Macula was normal in young patients and showed atrophic alteration in advanced stages. ERG was unrecordable in scotopic conditions and the cone responses were markedly hypovolted. Homozygosity mapping and whole exome sequencing identified a 4‐pb deletion, c.1154+3_1151+6delAAGT, located in the donor splice site of intron 8 of CERKL. The mutation impacts pre‐mRNA splicing of CERKL. This new deletion was present at a homozygous state in the two affected sons and was heterozygous in the parents. It was not present in the unaffected sister. Conclusions Mutations in CERKL gene have been reported in patients with retinitis pigmentosa, c.1154+3_1151+6delAAGT is a novel splicing variant associated with arRP. Extending the mutation spectrum of CERKL with additional families is important for genotype‐phenotype correlations.